Efficiency, effectiveness, and impacts assessment in the rail transport sector: a state‐of‐the‐art critical analysis of current research. (24th May 2018) - Catalano, Giuseppe; Daraio, Cinzia; Diana, Marco; Gregori, Martina; Matteucci, Giorgio
Abstract: This paper aims at being a comprehensive reference for stakeholders, policy makers, and scholars interested in analyzing the problem of efficiency, effectiveness, and impacts of rail transport systems in a sound empirical way, paying specific attention to passenger transport services. The paper combines different analytical frameworks (engineering, economics, impacts), systematic review techniques, and advanced mappings. Framing economic efficiency studies into a transport planning perspective permits to move from efficiency to effectiveness issues. In addition, including impacts offers a critical discussion of the existing empirical studies, relating them to the main methodological approaches used. This analysis can be useful for those interested in developing new techniques for the evaluation of this sector. The critical analysis developed in this paper provides a catalog of inputs, outputs, external factors, possible impacts to account for, data, and approaches, which allows us to identify areas in which new methodological developments, new approaches, are needed to address the relevant societal challenges of the rail transport sector.